Expanding the Cultural Turn in Culturepreneurship: A Gaze Towards Indonesia - Soeparto, Wahyudi Henky (Lakon : Jurnal Kajian Sastra dan Budaya, 2023)
Culturepreneurship is a growing subject in Indonesia and in many parts of the world. It is a multi- and trans-disciplinary studies that combines tenets of entrepreneurship and cultural analysis. However, the connexion between these two disciplines are often to be not in complementary. The logic of entrepreneurship still dominates and leaves the cultural aspect of the discipline to be in the periphery. This article attempts to argue the importance of the cultural turn within culturepreneurship by incorporating Cultural Studies into the discussion. Specifically, since it is an initial stage of such effort, this article looks into Raymond Williams' seminal contribution to Cultural Studies. His pioneering ideas on cultural materialism are the footing of later development of Cultural Studies. Other than theoretical discussions on Williams, the latter part of this article explores a case study of the 2022 Surabaya Great Expo to briefly manifest the attempt to do cultural turn in culturepreneurship.